The ADRN and the public’s voice: making administrative data available for research while gaining public trust: IJPDS (2017) Issue 1, Vol 1:155, Proceedings of the IPDLN Conference (August 2016) - Verwulgen, Ilse (International Journal of Population Data Science, 2017)
ABSTRACT Background This paper presents the way the Administrative Data Research Network (ADRN) has incorporated the results of public consultation into the core of its operations and policies. Administrative data are a rich source of information, but underused in social and economic research. In the past it has been very difficult to gain access to these datasets. The ADRN is a UK-wide initiative, funded by the Economic and Social Research Council (ESRC) in 2013. The Network facilitates secure research access to linked, de-identified administrative data to enable real-world analysis that can benefit society. Administrative data research can provide a solid evidence base for policy makers to evaluate the results of active policies or uncover new ways to tackle social problems. Approach Using government data for research is still a sensitive topic for the public, and rightly so. Amidst growing concerns about privacy and data security, the use of administrative data is a potentially controversial move. At the beginning of the project, the ESRC commissioned a nation-wide public consultation to gauge understanding of social research and reactions to the use of administrative data in research. Results The ADRN used the results of this consultation to incorporate mechanisms for lay participation as well as accountability towards the public into its governance, and makes a case for engaging the public without compromising the scientific integrity of the research it supports. Funded by the Economic & Social Research Council, the Administrative Data Research Network, set up as part of the UK Government’s Big Data initiative, is a UK-wide partnership between universities, government bodies, national statistics authorities and the wider research community. www.adrn.ac.uk